2018
DOI: 10.2147/ijn.s172906
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration effects of nanoencapsulated triterpenoids from petri dish-cultured <em>Antrodia cinnamomea</em> on reproductive function of diabetic male rats

Abstract: PurposeNanoencapsulated triterpenoids from petri dish-cultured Antrodia cinnamomea (PAC) and its amelioration effects on reproductive function in diabetic rats were investigated.Materials and methodsPAC encapsulated in silica–chitosan nanoparticles (Nano-PAC) was prepared by the biosilicification method. The diabetic condition in male Sprague Dawley rats was induced by high-fat diet and streptozotocin (STZ). Three different doses of Nano-PAC (4, 8, and 20 mg/kg) were administered for 6 weeks. Metformin and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…When examining oxidative stress parameters in the current study, it was determined that diabetes increased the MDA level, while decreased levels of GSH, activities of GSH.Px, CAT at fourth and eight weeks (Tables 1 and 2). These findings were found to be similar to the findings of studies (Armagan et al, 2006;Atta et al, 2017;Hassanzadeh-Taheri & Hosseini, 2019;Kermani et al, 2019;Sudirman et al, 2018;Zha et al, 2018), which reported that diabetes increased MDA levels and decreased antioxidant enzyme activities in testicular tissue. (Aksu et al, 2016;Cengiz et al, 2017;Daggulli et al, 2014;Shoorei et al, 2019).…”
Section: F I G U R E 19supporting
confidence: 90%
See 1 more Smart Citation
“…When examining oxidative stress parameters in the current study, it was determined that diabetes increased the MDA level, while decreased levels of GSH, activities of GSH.Px, CAT at fourth and eight weeks (Tables 1 and 2). These findings were found to be similar to the findings of studies (Armagan et al, 2006;Atta et al, 2017;Hassanzadeh-Taheri & Hosseini, 2019;Kermani et al, 2019;Sudirman et al, 2018;Zha et al, 2018), which reported that diabetes increased MDA levels and decreased antioxidant enzyme activities in testicular tissue. (Aksu et al, 2016;Cengiz et al, 2017;Daggulli et al, 2014;Shoorei et al, 2019).…”
Section: F I G U R E 19supporting
confidence: 90%
“…In many studies (Armagan et al, 2006;Atta et al, 2017;Kermani et al, 2019;Sudirman et al, 2018;Zha et al, 2018) conducted to examine the effects of diabetes on the male reproductive system, it has been reported that MDA levels increase in testicular tissue due to the insufficient enzymatic or non-enzymatic antioxidants. When examining oxidative stress parameters in the current study, it was determined that diabetes increased the MDA level, while decreased levels of GSH, activities of GSH.Px, CAT at fourth and eight weeks (Tables 1 and 2).…”
Section: F I G U R E 19mentioning
confidence: 99%
“…22 A previous study reported that triterpenoid compound from petri dish-cultured Antrodia cinnamomea ameliorates male reproductive function in rat model. 23 A previous study reported that besides the triterpenoids and polysaccharides, antroquinonol also present in solid-state fermentation of mycelium of A. cinnamomea. 24 It also can be extracted by ethanolic extraction from mycelium of A. cinnamomea.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, silica and chitosan have been reported by various previous studies relate their ability to enhance the bioavailability of some low soluble materials, such as triterpenoids and curcumin. 23,34 Therefore, we hypothesized that the nanoparticle form of antroquinonol enhances its utilization. As such, this study aimed to characterize the chitosan-silicate nanoparticle of antroquinonol-rich extract from solid-state-cultured A. cinnamomea (nano-SAC) and to investigate its ameliorative effects on male reproduction function in high-fat diet and streptozotocin-induced type-2 diabetic rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbitane-type triterpenoids were reported to improve insulin sensitivity and glucose homeostasis in C2C12 myotubes and a streptozotocin (STZ)-induced diabetic mouse model [4]. Nanoencapsulated triterpenoids from Petri dish-cultured Antrodia cinnamomea ameliorate hyperglycemia on high-fat diet (HFD)- and STZ-induced diabetic rats [5]. The extract of a triterpenoid-enriched Jamun fruit attenuates hyperglycemia and glucose intolerance, prevents the abnormal elevation of hepatic gluconeogenesis, and improves dyslipidemia in STZ-induced diabetic mice [6].…”
Section: Introductionmentioning
confidence: 99%